Digitalisasi Perdagangan : Tantangan dan Peluang untuk Indonesia di Era Industri - Lasiyono, Untung; Yasmin, Risti Aprilia; Yulia, Sazy; Larasati, Ameilia (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2025)
The digitalization of trade has brought major changes to the business world in Indonesia. However, the digital divide that is still widespread is a major barrier for MSMEs to participate in the digital economy. This research explores the factors that cause the digital divide in Indonesia, such as access to infrastructure, digital literacy, and government support. Case studies conducted on a number of MSMEs in rural and urban areas reveal that lack of access to high-speed internet, limited digital skills, and high operational costs are the main challenges. Apart from that, this research also highlights various government initiatives in overcoming the digital divide and provides policy recommendations to accelerate digital inclusion for MSMEs.